Resources: Agriculture and food security - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
IFPRI’s mission is to provide research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition. Recent publications and websites provide critical data and analysis on agricultural policies and food security.